Finite amplitude pressure wave propagation in chemically active heterogeneous media - Vakhguelt, A. (Nazarbayev University, 2014)
This paper presents a mathematical analysis of pressure wave propagation in gas media containing particles and proposed mathematical model of the process.
Keywords: chemically active; heterogeneous media; gas; media